2006
DOI: 10.1097/00000478-200608000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Sarco/Endoplasmic Reticulum Calcium-ATPase 2 Expression as a Tumor Marker in Colorectal Cancer

Abstract: Maintaining a high calcium concentration in the endoplasmic reticulum through the action of sarco/endoplasmic reticulum calcium-ATPases (SERCAs) is crucial in many cell functions involved in intracellular signal transduction, control of proliferation, programmed cell death, or the synthesis of mature proteins. Recent studies have found that many SERCAs have altered expression patterns in various malignancies. The purpose of the current study was to quantify the expression of SERCA2 in colorectal cancer (CRC) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 23 publications
4
19
0
2
Order By: Relevance
“…Alterations in calcium-dependent signaling are involved in cell proliferation and differentiation, apoptosis, and disruption of calcium homeostasis, which may contribute to cancer development. Chung and colleagues have reported that elevated SERCA2 mRNA was detected in 90% of human colorectal cancer tissues, indicating the possible role of SERCA2 in the development and progression of human colorectal cancer (31). On the other hand, a null mutation in 1 copy of the SERCA2 has been shown to lead to squamous cell tumor in mice, suggesting that the proper amount of SERCA2 is crucial for the destiny of cells (32).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in calcium-dependent signaling are involved in cell proliferation and differentiation, apoptosis, and disruption of calcium homeostasis, which may contribute to cancer development. Chung and colleagues have reported that elevated SERCA2 mRNA was detected in 90% of human colorectal cancer tissues, indicating the possible role of SERCA2 in the development and progression of human colorectal cancer (31). On the other hand, a null mutation in 1 copy of the SERCA2 has been shown to lead to squamous cell tumor in mice, suggesting that the proper amount of SERCA2 is crucial for the destiny of cells (32).…”
Section: Discussionmentioning
confidence: 99%
“…SERCA2 mRNA is shown over-expressed in cancerous tissues compared to normal tissue, which is also positively correlated to invasion and metastasis. In addition, high SERCA2 is associated with poor clinical outcome and metastasis in cancer patients [30]. SERCA2b, another ATPase, decreases with retinoic acid induced differentiation [31] indicating there is an inverse relationship between immune cell differentiation and ATPases.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies investigated the expression of SERCA in normal and tumor tissue reporting downregulation of this ATPase in cancer [ 8 - 11 ]. But, in colorectal cancer, Chung et al reported that SERCA 2 mRNA was increased compared to normal tissue [ 12 ]. Moreover, increased SERCA 2 protein levels were correlated with serosal invasion, lymph node metastasis, advanced tumor stage and poorer survival-rate.…”
Section: Discussionmentioning
confidence: 99%